A set of engineered Escherichia coli expression strains for selective isotope and reactivity labeling of amino acid side chains and flavin cofactors. - Jennifer Mehlhorn (Public Library of Science (PLoS), 2013)
Biological reactions are facilitated by delicate molecular interactions between proteins, cofactors and substrates. To study and understand their dynamic interactions researchers have to take great care not to influence or distort the object of study. As a non-invasive alternative to a site-directed mutagenesis approach, selective isotope labeling in combination with vibrational spectroscopy may be employed to directly identify structural transitions in wild type proteins. Here we present a set of customized Escherichia coli expression strains, suitable for replacing both the flavin cofactor and/or selective amino acids with isotope enriched or chemically modified substrates. For flavin labeling we report optimized auxotrophic strains with significantly enhanced flavin uptake properties. Labeled protein biosynthesis using these strains was achieved in optimized cultivation procedures using high cell density fermentation. Finally, we demonstrate how this approach is used for a clear assignment of vibrational spectroscopic difference signals of apoprotein and cofactor of a flavin containing photoreceptor of the BLUF (Blue Light receptors Using FAD) family.